The Role of Surface Text Processing in Centrality Deficit and Poor Text Comprehension of Adolescents with Attention Deficit Hyperactivity Disorder: A Think‐Aloud Study. Issue 1 (15th January 2021) - Yeari, Menahem; Lavie, Anat
Abstract: The present study employed a think‐aloud method to explore the origin of centrality deficit (i.e., poor recall of central ideas) in individuals with Attention Deficit Hyperactivity Disorder (ADHD). Moreover, utilizing the diverse think‐aloud responses, we examined the overall quality of text processing employed by individuals with ADHD during reading, in order to shed more light on text‐level deficiencies underlying their poor comprehension after reading. To address these goals, adolescents with and without ADHD were asked to state aloud whatever comes to their minds during the reading of two expository texts. After reading, the participants freely recalled text ideas and answered multiple‐choice questions on the texts. Compared to controls, participants with ADHD generated fewer responses that reflect deep, efficient text processing, and reinstated fewer prior text ideas, particularly central ones, during reading. Moreover, the proportions of deep processing responses positively associated with participants' performance on recall and comprehension tasks. These findings suggest that individuals with ADHD exhibit poor text comprehension and memory, particularly of central ideas, because they construct a low‐quality, less‐connected text representation during reading, and produce fewer, less‐elaborated retrieval cues for subsequent tasks after reading.